Changes in cytokinins are sufficient to alter developmental patterns of defense metabolites in Nicotiana attenuata - Brütting, Christoph; Schäfer, Martin; Vanková, Radomíra; Gase, Klaus; Baldwin, Ian T; Meldau, Stefan (The Plant journal, 2017)
Plant defense metabolites are well known to be regulated developmentally. The optimal defense (OD) theory posits that a tssue's fitness values and probability of attack should determine defense metabolite allocations. Young leaves are expected to provide a larger fitness value to the plant, and therefore their defense allocations should be higher when compared with older leaves. The mechanisms that coordinate development with defense remain unknown and frequently confound tests of the OD theory predictions. Here we demonstrate that cytokinins (CKs) modulate ontogeny-dependent defenses in Nicotiana attenuata. We found that leaf CK levels highly correlate with inducible defense expressions with high levels in young and low levels in older leaves. We genetically manipulated the developmental patterns of two different CK classes by using senescence- and chemically inducible expression of CK biosynthesis genes. Genetically modifying the levels of different CKs in leaves was sufficient to alter ontogenic patterns of defense metabolites. We conclude that the developmental regulation of growth hormones that include CKs plays central roles in connecting development with defense and therefore in establishing optimal patterns of defense allocation in plants.
Keywords: cyklopentany; Animals; herbivores; optimal defense; nemoci rostlin; Cyclopentanes; geneticky modifikované rostliny; immunosenescence; inducible defense; Manduca; listy rostlin; oxylipiny; Herbivory; Plants, Genetically Modified; Manduca sexta; Plant Proteins; Time Factors; časové faktory; Nicotiana; Nicotiana attenuata; Host-Parasite Interactions; interakce hostitele a parazita; Plant Leaves; plant development; cytokininy; Cytokinins; Acetates; rostlinné proteiny; Oxylipins; acetáty; phytohormones; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; Plant Diseases; býložravci; regulátory růstu rostlin; zvířata; tabák; Plant Growth Regulators; cytokinins